Differences between thin films deposition systems in the production transition metal nitride (2013)
The progress in vacuum technology have enabled the development of advanced coatings processes such as plasma assisted systems, which can produce thin films of different composition and optimum properties, that cannot be collected for the same material. The techniques of Pulsed Arc, Ionic Implantation and Sputtering have differences to produce coatings. Currently, AuN films have been grown by different techniques such as ion implantation, Reactive Ion Sputtering and Pulsed Arc, which have differences in the grown of the film. Siller 2002 reported a binding energy of 396.6 eV to N1s narrow spectrum as the first direct observation of a gold nitride. In this work, AuN thin films were grown in a system Plasma-Assisted Physical Vapor Deposition by pulsed arc technique. A N1s spectra was obtained with binding energies of 398.1, which by means of the differences between the techniques of ion implantation, sputtering and pulsed arc is concluded have been assigned to gold nitride species.